Evaluating the impact of responsible investing strategies on fund performance - Ntuli, Thulani (Rhodes University, Faculty of Commerce, Rhodes Business School, 2017)
Several studies have been undertaken to evaluate performance of responsible investments, that is, funds that integrate ethical as well as environmental, social and governance considerations in the investment process (ESG). Particularly to address the question whether it is possible for investors to do well while doing good. Modern Portfolio Theory predicts sub-optimal performance for funds constructed on any basis other than risk-reward optimisation. These studies usually compare performance of responsible investments with conventional funds or an unrestricted benchmark portfolio. The findings have been contradictory and on the main inconclusive. Underlying this contradiction is the treatment of responsible investments funds as a homogenous group of funds and not acknowledging their heterogeneity owing to methods and strategies used to construct them. This study seeks to address this gap in the literature by investigating the impact of responsible investment strategies on fund performance. The performance of nine South African responsible investment funds constructed and manged using different responsible investing strategies are analysed over a five-year period from 01 October 2010 to 31 October 2015. Their performance is benchmarked against the JSE ALL Share Index (ALSI) and the FTES/JSE SRI index. Specifically, the average monthly returns, variability and Sharpe ratio of the constituent fund is used to compare performance. Moreover, the CAPM based Jensen alpha is used to determine any significant under or overperformance of respective funds relative to the benchmarks. The study found to be no difference in average monthly returns and risk relative to the two benchmark indices for all respective strategies. However, funds constructed using the negative screening strategy generally underperform. These funds overall deliver a statistically significant lower alpha. It is concluded that this RI investing strategy is not suitable for investors concerned about a trade-off between fund performance and ESG performance.
Keywords: Uncatalogued